Inquisidores, exorcistas y obsesos en la América colonial: El caso de Luisa Benítez y las monjas clarisas de Trujillo (Perú) - Paz Torres, Margarita (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Palaeographic and criticaledition of a fragment of theprocess of faith of thenuns of theconvent of Santa Clara de Trujillo (Peru), a copy of whichislocated in the AHNM (NationalHistorical Archive of Madrid). Commentonphilological, literary, and anthropologicalaspects of this 17TH-centurymanuscript.